(untitled) (PILAR, 2025)
This article elaborates the methodological framework of sanad criticism as one of the primary instruments in assessing the authenticity of the Prophet’s hadith. Sanad criticism serves as a scientific mechanism to ensure the reliability of transmission chains by examining the personal integrity and intellectual capacity of narrators, as well as their connectivity across generations. Through a structured analytical approach, this study presents the conceptual foundations of sanad criticism, major and minor criteria of authentication, and practical stages applied by hadith scholars-namely takhrij, i‘tibar, narrator evaluation, and concluding authenticity judgment. The study highlights that a valid sanad must fulfill five core criteria: continuity, the narrator’s integrity (‘adalah), precision (dhabit), freedom from irregularities (shudhudh), and absence of hidden defects (‘illah). This article, therefore, affirms that sanad criticism constitutes an indispensable instrument in hadith authentication and remains relevant as a scientific discipline within Islamic studies.